The Development of a Real-Time Recombinase-Aid Amplification Assay for Rapid Detection of African Swine Fever Virus - Wu, Yongshu; Yang, Yang; Ru, Yi; Qin, Xiaodong; Li, Miaomiao; Zhang, Zhixiong; Zhang, Rui; Li, Yijing; Zhang, Zhidong; Li, Yanmin (Frontiers in Microbiology, 2022)
African swine fever (ASF), caused by the African swine fever virus (ASFV), is an acute, deadly, infectious disease of domestic pigs and wild boars and has a tremendous negative socioeconomic impact on the swine industry. ASF is a notifiable disease to the World Organization for Animal Health (OIE). Currently, no effective vaccine or treatment against ASF is available. Early detection and rapid diagnosis are potentially significant to control ASF spread with the emerging ASFV mutant strains and non-classical symptoms. In this study, we developed a real-time recombinase-aid amplification (RAA) assay to detect the ASFV genome rapidly. Thirty samples were detected using commercial lysis buffer for DNA extraction and equipped with a portable testing instrument. The results showed that the sensitivity of RAA was 103 copies per reaction at 95% probability in 9 min at 39°C. The method was universally specific for three strains of ASFV, and there was no cross-reaction with other pathogens, including foot-and-mouth disease virus (FMDV), classical swine fever virus (CSFV), porcine reproductive and respiratory syndrome virus (PRRSV), porcine circovirus 2 (PCV2), pseudorabies virus (PRV), and porcine parvovirus (PPV). The coefficient of variation (C.V) of repetitive experiments was 0%, and the coincidence rate was 100% compared to the real-time qPCR. 123 field samples were detected by the real-time RAA assay, and the results showed that the clinical coincidence rate of the real-time RAA assay was 98% compared to the real-time qPCR assay. The advantages of this method were as follows: the extraction of DNA can be performed on site, the DNA template is directly used, a small battery-powered instrument is easily available, and the on-site diagnostic process is finished within an hour. These suggest that this assay could be used to detect different genotypes of ASFV and play a vital role in the control of ASF.